(sin(180°+2x))/(1+cos2x)*(cos2x0/(cos(90°+x))=

来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/03 12:30:23
(sin(180°+2x))/(1+cos2x)*(cos2x0/(cos(90°+x))=(sin(180°+2x))/(1+cos2x)*(cos2x0/(cos(90°+x))=(sin(180

(sin(180°+2x))/(1+cos2x)*(cos2x0/(cos(90°+x))=
(sin(180°+2x))/(1+cos2x)*(cos2x0/(cos(90°+x))=

(sin(180°+2x))/(1+cos2x)*(cos2x0/(cos(90°+x))=
(sin(180°+2x))/(1+cos2x)*(cos2x0/(cos(90°+2x))
=[-sin2x/(1+cos2x)][cos2x/(-sinx)]
=(sin2xcos2x)/(sinx(1+cos2x))
=(sin2xcos2x)/[2snxcos²x]
=(sin2xcos2x)/sin2xcosx
=cos2x/cosx